INFLUENCE OF PROJECT MACRO PLANNING PROCESS ON PERFORMANCE OF GATED COMMUNITY HOUSING PROJECTS IN NAIROBI COUNTY, KENYA - Musyoka, Michael Chris; Gakuu, Prof. Christopher; Kyalo, Dr. Dorothy Ndunge (IJRDO - Journal of Applied Management Science, 2017)
The principal objective of this was to examine the influence of project macro planningprocess on performance of gated community housing projects in Nairobi County, Kenya.The study population comprised of all active gated community housing projects initiatedin 2009 – 2014. A total of 572 respondents were drawn from 143 sampled gated communityhousing projects from the seventeen sub-counties of Nairobi County using census,stratified, simple random, and purposive sampling techniques. A standardized open endedinterview guide and a questionnaire with both open and closed-ended items were used tocollect data. Descriptive statistics showed that projects macro planning process had aninfluence on performance of gated community housing construction projects.The value ofr2 was 0.429, indicating that project macro planning process explained42.9% of thevariation in the performance in gated community housing projects in Nairobi County,Kenya. The β coefficient was 0.655, indicating that project macro planning process hadstatistically significant influence on the performance of gated community housing projects(β=0.655, t=10.962, p=0.000<0.05). The β value implied that every unit change on theperformance of gated community housing projects is associated with 65.5% changes inproject macro planning process.